2015
DOI: 10.1016/j.ygyno.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of ovarian malignancy algorithm for the conservative management of women with a pelvic mass

Abstract: Objective To evaluate the use of as an aid in the identification of women who can safely undergo conservative, non-surgical management. Methods All patients referred to the Program in Women’s Oncology for surgery with a pelvic mass are evaluated at a prospective multidisciplinary tumor board (TB) where ROMA and imaging are used for management recommendations. This study evaluated women presented to TB with a pelvic mass between 2009 and 2013 who had either surgical or conservative management. Results Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…For example, while carcinoma antigen 125 (CA125) alone has not been recommended for screening for ovarian carcinoma [29], Lokich et al could show that the combination of CA125 with HE4, using the Risk of Ovarian Malignancy Algorithm (ROMA), might more accurately define the risk of an epithelial ovarian carcinoma, which would prompt a more aggressive diagnostic workup (e.g., laparoscopy) versus a more conservative management strategy of surveillance in low risk women [30]. Furthermore, the recent data on lung cancer screening in high risk individuals using low resolution computed tomography has shown a mortality benefit on a population basis [31].…”
Section: Role Of Tms In Current Clinical Practicementioning
confidence: 99%
“…For example, while carcinoma antigen 125 (CA125) alone has not been recommended for screening for ovarian carcinoma [29], Lokich et al could show that the combination of CA125 with HE4, using the Risk of Ovarian Malignancy Algorithm (ROMA), might more accurately define the risk of an epithelial ovarian carcinoma, which would prompt a more aggressive diagnostic workup (e.g., laparoscopy) versus a more conservative management strategy of surveillance in low risk women [30]. Furthermore, the recent data on lung cancer screening in high risk individuals using low resolution computed tomography has shown a mortality benefit on a population basis [31].…”
Section: Role Of Tms In Current Clinical Practicementioning
confidence: 99%
“…Approximately 289,000 women in the United States are diagnosed with a pelvic mass each year [2]. When patients are diagnosed with pelvic masses, the first and most important thing is to determine the origin of the masses and then to evaluate whether they are benign or malignant.…”
Section: Introductionmentioning
confidence: 99%
“…Their results confirmed that nonsurgical management should be considered for SOC identified with ultrasonography and negative ROMA and CA125 levels. 14 The patients qualified for fine-needle aspiration at our department presented SOC under 80 mm in diameter. Cysts with diameters above 80 mm were qualified for surgery.…”
Section: Discussionmentioning
confidence: 99%